DAMPAK KURS, INFLASI DAN SUKU BUNGA PADA EKSPOR NON-MIGAS INDONESIA KE ASEAN - TAMPUBOLON, ARSYAF (JEBIM Prima, 2024)
This study was conducted to analyze the factors that can affect the growth of Indonesia's non-oil and gas exports to ASEAN countries. The dependent variable used in this study is non-oil and gas exports and the dependent variables are the dollar exchange rate, inflation rate and BI interest rate. The research was conducted in Indonesia with the data taken is the period from 2010 to 2023. The data source used is secondary data sourced from the Indonesian Central Bureau of Statistics, and Bank Indonesia. Data analysis uses the help of e-views software by conducting multiple regression analysis tests. The results of this study apparently prove that the variables of dollar exchange rate, inflation and BI interest rate affect Indonesia's non-oil and gas exports to ASEAN countries..